2021
DOI: 10.3390/app11209697
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Cnidoscolus aconitifolius (Mill.) Ethyl Acetate Extract on Croton Oil-Induced Mouse Ear Edema

Abstract: Nowadays, there is a growing interest in the development of medicinal plant-based therapies to diminish the ravages of the inflammatory process related to diseases and tissue damage. Most therapeutic effects of these traditional medicinal plants are owed to their phenolic and antioxidant properties. C. aconitifolius is a traditional medicinal plant in Mexico. Previous characterization reports have stated its high nutritional and antioxidant components. The present study aimed to better understand the biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, there was periportal infiltration of inflammatory cells with mild fibrosis in extract treated groups, however, hepatocytes were moderately congested and hepatic features were preserved and kept (Slide). Padilla-Camberos et al, (2021) expounded the anti-inflammatory properties of Cnidoscolus aconitifolius of which its bioactive components have been implicated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was periportal infiltration of inflammatory cells with mild fibrosis in extract treated groups, however, hepatocytes were moderately congested and hepatic features were preserved and kept (Slide). Padilla-Camberos et al, (2021) expounded the anti-inflammatory properties of Cnidoscolus aconitifolius of which its bioactive components have been implicated.…”
Section: Resultsmentioning
confidence: 99%
“…Its treatment value ranges from the capacity to improve vision, neutralize scorpion stings, manage insomnia, and eliminate gout (Jensen, 1997, Atuahene et al, 1999. Other studies have demonstrated the application of C. aconitifolius in alcoholism, diabetes mellitus, obesity, kidney stones, hemorrhoids (Diaz-Bolio, 1975;Kuti andTorres, 1996, Mordi, 2012) and antiinflammation (Padilla-Camberos et al, 2021). Recently, the phenolic and amino acid composition of Ethiopian Chaya (Cnidoscolus chayamansa) was documented (Temesgen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In [3], the anti-inflammatory activity of Cnidoscolus aconitifolius was presented using an ethyl acetate extract, and the role of flavonoid content was determined in this study. The anti-inflammatory effect of C. aconitifolius extract was determined using the mouse ear edema test induced by the activities of croton oil.…”
Section: Issue Contentsmentioning
confidence: 99%
“…The finding observed from this study may be corroborated by well-established evidence, which suggests the two plants (O. suave and C. aconitifolius) where the endophytes (C. tropicalis and P. capitalensis) were isolated are validated medicinal plants. 26,27 The medicinal plant, O. suave, has been demonstrated to have antioxidant properties due to the high con-tent of flavonoids and polyphenols secondary metabolites, which are said to have cytoprotection effect. 28 Also, essential oil from O. suave was demonstrated to have antimicrobial activity against pathogens.…”
Section: Antimicrobial Activity Of Endophytic Fungi Crude Extractsmentioning
confidence: 99%